1996
DOI: 10.1084/jem.183.6.2551
|View full text |Cite
|
Sign up to set email alerts
|

Differential cytokine effects on primitive (CD34+CD38-) human hematopoietic cells: novel responses to Flt3-ligand and thrombopoietin.

Abstract: SummaryA high proportion of the CD34+CD38 -cells in normal human marrow are defined as longterm culture-initiating cells (LTC-IC) because they can proliferate and differentiate when cocultured with cytokine-producing stromal feeder layers. In contrast, very few CD34+CD38 -cells will divide in cytokine-containing methylcellulose and thus are not classifiable as direct colony-forming cells (CFC), although most can proliferate in serum-free liquid cultures containing certain soluble cytokines. Analysis of the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
193
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 330 publications
(214 citation statements)
references
References 28 publications
17
193
1
3
Order By: Relevance
“…Indeed, data reported so far on LTC-IC amplification are limited to incubation periods of a few weeks. [16][17][18] In our experiments, after a 2 week-incubation, the magnitude of LTC-IC expansion did not appear to be different for several growth factor combinations. However, when the same culture conditions were prolonged, quite the opposite occurred with the LTC-IC pool, in that only a few growth factor combinations could further amplify it, while others would lead to its exhaustion.…”
Section: Figurementioning
confidence: 55%
See 3 more Smart Citations
“…Indeed, data reported so far on LTC-IC amplification are limited to incubation periods of a few weeks. [16][17][18] In our experiments, after a 2 week-incubation, the magnitude of LTC-IC expansion did not appear to be different for several growth factor combinations. However, when the same culture conditions were prolonged, quite the opposite occurred with the LTC-IC pool, in that only a few growth factor combinations could further amplify it, while others would lead to its exhaustion.…”
Section: Figurementioning
confidence: 55%
“…17 The most relevant finding that emerges from our experiments is that a completely different situation is observed when the suspension cultures are extended for prolonged periods of time. The kinetics of LTC-IC expansion demonstrated that the stem cell pool could be further expanded by increasing the length of incubation: afer a 5-week incubation only some growth factor combinations could sustain a prolonged and increasingly greater expansion of LTC-IC.…”
Section: Figurementioning
confidence: 67%
See 2 more Smart Citations
“…Soluble forms activate the corresponding FLT3 receptor [3] Although its messenger RNA is detected in most hematopoietic and nonhematopoietic tissues, protein expression is restricted to T lymphocytes and BM stromal cells composing the hematopoietic microenvironment [15][16][17]. Generally, FL acts in combination with other cytokines, resulting in strongly synergistic effects; isolated addition of FL to stem/progenitor cell cultures has no significant effect on proliferation of myeloid and lymphoid progenitors [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%